PERSEPSI PELANGGAN TERHADAP SERVICE QUALITY GARUDA INDONESIA AIRLINES - Linawati Linawati; Tri Mulyani Setyowati (Institut Transportasi dan Logistik Trisakti, 2015)
The purpose of the research is to analyze the customers’ satisfaction of Garuda Indonesia. It is hoped that by giving Service Quality, the passengers of Garuda Indonesia will perform loyalty and always fly with the airlines. This research is using primary data from 100 respondents of Garuda Indonesia’s passengers. The data is collected by distributing questionnaires to the respondents. The research variables are taken from service quality (SERVQUAL) and Customer Satisfaction. Then the data is analysed with quantitative analysis by scoring and calculating the percentage of both variables. Based on the result, each score of attribution of the service quality has given outstanding value. The passengers are satisfied with the service given by Garuda Indonesia. The service quality which consists of five different variables: tangibles, reliability, responsiveness, assurance, and empathy has shown the significance attribution of the customer satisfaction with the highest score achieved is Responsiveness (17, 13%).